Markers and mechanisms of death in Drosophila - Tower, John (Frontiers in Aging, 2023)
Parameters correlated with age and mortality in Drosophila melanogaster include decreased negative geotaxis and centrophobism behaviors, decreased climbing and walking speed, and darkened pigments in oenocytes and eye. Cessation of egg laying predicts death within approximately 5 days. Endogenous green fluorescence in eye and body increases hours prior to death. Many flies exhibit erratic movement hours before death, often leading to falls. Loss of intestinal barrier integrity (IBI) is assayed by feeding blue dye (“Smurf” phenotype), and Smurf flies typically die within 0-48 hours. Some studies report most flies exhibit Smurf, whereas multiple groups report most flies die without exhibiting Smurf. Transgenic reporters containing heat shock gene promoters and innate immune response gene promoters progressively increase expression with age, and partly predict remaining life span. Innate immune reporters increase with age in every fly, prior to any Smurf phenotype, in presence or absence of antibiotics. Many flies die on their side or supine (on their back) position. The data suggest three mechanisms for death of Drosophila. One is loss of IBI, as revealed by Smurf assay. The second is nervous system malfunction, leading to erratic behavior, locomotor malfunction, and falls. The aged fly is often unable to right itself after a fall to a side-ways or supine position, leading to inability to access the food and subsequent dehydration/starvation. Finally, some flies die upright without Smurf phenotype, suggesting a possible third mechanism. The frequency of these mechanisms varies between strains and culture conditions, which may affect efficacy of life span interventions.